Intramedullary nailing of humeral shaft fractures - Sanzana, E. (Springer-Verlag, 2002)
From 1996 until 2000 we treated 52 humeral shaft fractures with AO unreamed nailing. Mean patient age was 35.8 years and the average follow-up 29.6 months. There were 31 type A fractures, 15 type B, and 6 type C. Closed retrograde nailing was performed in 46 cases and open nailing in six. Functional results were excellent in 48 cases, moderate in three, and poor in one.